2020
DOI: 10.1111/vsu.13556
|View full text |Cite
|
Sign up to set email alerts
|

Crimped monofilament nylon leader for median sternotomy closure in 10 dogs

Abstract: Objective: To describe and report the outcomes after closure of median sternotomies with crimped monofilament nylon leader (MNL) in dogs. Study design: Retrospective observational study. Animals: Dogs (n = 10) that underwent intrathoracic surgery through a median sternotomy approach. Methods: The median sternotomy was closed in a peristernal figure eight pattern with crimped MNL. Medical records were reviewed for clinical and histopathological findings and complications. Owners or veterinarians were contacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…15 The same has been shown with the use of crimped nylon leader (40 or 80 lb) in dogs varying 12-38 kg. 14 The estimated risk of developing a closure-related complication, while taking into account other known or potential risk factors, such as dog weight, was equivalent between groups in our study. It therefore supports the conclusion that closure of MS with suture and wire are both suitable options in dogs including those of large (≥20 kg) size.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…15 The same has been shown with the use of crimped nylon leader (40 or 80 lb) in dogs varying 12-38 kg. 14 The estimated risk of developing a closure-related complication, while taking into account other known or potential risk factors, such as dog weight, was equivalent between groups in our study. It therefore supports the conclusion that closure of MS with suture and wire are both suitable options in dogs including those of large (≥20 kg) size.…”
Section: Discussionmentioning
confidence: 55%
“…A previously performed biomechanical study has shown that suture (four metric polydioxanone) could provide as effective closure of the sternum as orthopedic wire (12 gauge) in 12 greyhounds 15 . The same has been shown with the use of crimped nylon leader (40 or 80 lb) in dogs varying 12–38 kg 14 . The estimated risk of developing a closure‐related complication, while taking into account other known or potential risk factors, such as dog weight, was equivalent between groups in our study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation